PENGENALAN DAN PENGEMBANGAN PENGETAHUAN TERHADAP BUDAYA INDONESIA KEPADA SISWA DI SEKOLAH INTERNATIONAL BALI - Putu Gede Budiartha; Wayan Nurita; Ni Made Dwi Kusuma , Wardani, (LOKATARA SARASWATI, 2024)
This community service aims to introduce and provide broader knowledge about the culture and traditions originating from Indonesia. This is intended to develop children's knowledge from various countries about Indonesia. The location of target children are students who attend the Kids Club at Parklife (PT. Taman Jiwa) Bali which is located on Jalan Raya Uma Buluh No. 15, Canggu, North Kuta District, Badung Regency, Bali. Kids Club, which is a school and daycare, is an option for parents who come to Bali in a short time. The problem faced by students and teachers is the lack of knowledge of students from various countries about Indonesia. Kids Club, which is a school and daycare, is an option for parents who come to Bali in a short time. The target of this activity is Kids Club students at Parklife Bali with an age range of 3-10 years. Conducting activities and events to introduce